Estruturas de mercado e custos de transação no setor de beneficiamento de leite - Ciechowicz, Izis Freire Santos (2019)
The milk production chain is of great economic and social importance for the state of Rio Grande do Sul and in recent years has been undergoing transformations, greatly influenced by productive, institutional and socioeconomic factors. The objective of the present study was to analyze the sources of transaction costs and the behaviors inherent to dairy products in the markets of Rio Grande do Sul. In this sense, the research sought to describe the characteristics of dairy products operating in Brazil and RS, also identified which is the degree of market concentration of the main dairy products in Brazil, as well as analyzed the nature of the transaction costs and the behaviors adopted by the dairy products operating in the milk market of the northwest region of Rio Grande do Sul. The research is quantitative, due to the market concentration calculations, using secondary data from Leite Brasil and Embrapa platforms from 2007 to 2018 and qualitative as a result of content analysis, using a database based on semi-structured script applied Dairy Managers from May to June 2019. In recent years, the Brazilian dairy market, despite having competitive companies that process high quantities of milk, has a low market concentration. As for the sources of transaction costs, it is inferred that these are mainly due to conflicts over the price paid per liter of milk to the rural producer, quality of the raw material and commercial wear. The conducts to minimize the effects of costs occur through interpersonal relationships, technical assistance and compensation for quantity supplied and milk quality.